La photographie comme processus performatif - Richard Shusterman (Appareil)
In this article originally published in 2012, R. Shusterman argues that photography is not limited to the photograph, which is merely its final two-dimensional product, developed, printed, or digitally displayed. Focusing on the example of the portrait photography, he explores what happens before the photograph, in order to highlight the performative dimension of an art form often conceived as strictly visual. Indeed, both the photographer, in taking the photo, and the subject, in posing for it, engage in performative, somatic, and sometimes intense dramatic processes. The photographer must orient his camera, which supposes a certain somatic control of his position, his posture and his balance. He can choose or create an atmosphere, a staging or a situation sometimes complex. Additionally, he must communicate with the subject being photographed to make him feel at ease or in the appropriate state of mind. As for the photographed subject, he takes the pose, which can be assimilated to an actor’s performance: depending on what he wants to reveal about himself, he stylizes himself, (re)presents and shapes his image. Ultimately, photography initiates a true dramatic process, in the sense that it focuses our attention on the events or people being photographed, placing them in a privileged frame that sets them apart and intensifies their presence, without disconnecting them from the flow of ordinary life. R. Shusterman cites examples of this dramatization in photographs of certain ritual events, such as weddings or graduations ceremonies.